Theatrics of transnational criminal justice: Ethnographies of penality in a global age - Sausdal, David (Theoretical criminology, 2021)
This special issue sets out to explore the Theatrics of Transnational Criminal Justice. ‘Why’, we ask, ‘do transnational criminal justice actors perform themselves as they do?’ ‘Why are their representations frequently, if not different from, then often quite dramatized versions of the average reality of their practices?’ ‘What does such dramatization tell us about not only the symbolism but also the structure and state of transnational criminal justice?’ And, more generally, ‘what do such performances of transnational criminal justice reveal about the nature of penal power in a global day and age?’ In probing such questions, the special issue draws together a number of accomplished ethnographers who have been exploring the performative nature of transnational criminal justice issues around the world, considering both international bodies such as Frontex, Europol, UNODC, the ICC as well as the many national actors involved in the prevention, policing and prosecution of border-crossing issues.